Webinar Socialization of Presidential Regulations Related to Digital Transformation and Strengthening Economic Foundations in Digitalization Era - Khaddafi, Muammar; Heikal, Mohd.; F, Falahuddin; Ichsan, Ichsan; F, Fuadi; D, Damanhur; Fauzul Hakim Hasibuan, Ahmad; M, Munandar; Chalirafi, Chalirafi; Nur Ilham, Rico (RADJA PUBLIKA, 2021)
The Industrial Revolution is indeed familiar, Indonesia has known that the 4.0 industrial revolution has existed since 2011 but has been implemented by the Indonesian government since 2019. Currently, Indonesia in terms of its economy often associates it with the Industrial Revolution. The Industrial Revolution is a change that occurs rapidly in the implementation of the production process or the way of making or increasing the use value of an item that originally used human power (traditional) to use machine tools (modern). The purpose of this community service is to help the community in implementing, being able to implement digitalization in everyday life and being able to develop it. People really need to know how important technology is in today's era. This activity is designed for 1 day starting with the socialization of presidential regulations on digital transformation, how to strengthen the economic foundation in the digitalization era and consumer behavior towards the digitalization era. The preparation for the socialization which was held through this webinar was preceded by coordination and communication with the Governor of the Riau Islands, the leadership of Bank Indonesia and the Head of the Doctoral Program in Human Resource Management at the University of Batam. The results of this activity are in line with what is expected, namely the activities carried out can help the community in preparing themselves and developing themselves in order to compete in the era of digitalization transformation. how to strengthen the economic foundation in the digitalization era and consumer behavior towards the digitalization era. The preparation for the socialization which was held through this webinar was preceded by coordination and communication with the Governor of the Riau Islands, the leadership of Bank Indonesia and the Head of the Doctoral Program in Human Resource Management at the University of Batam. The results of this activity are in line with what is expected, namely the activities carried out can help the community in preparing themselves and developing themselves in order to compete in the era of digitalization transformation. how to strengthen the economic foundation in the digitalization era and consumer behavior towards the digitalization era. The preparation for the socialization which was held through this webinar was preceded by coordination and communication with the Governor of the Riau Islands, the leadership of Bank Indonesia and the Head of the Doctoral Program in Human Resource Management at the University of Batam. The results of this activity are in line with what is expected, namely the activities carried out can help the community in preparing themselves and developing themselves in order to compete in the era of digitalization transformation.